2002
DOI: 10.1177/004051750207200803
|View full text |Cite
|
Sign up to set email alerts
|

Thermoformable Automotive Composites Containing Kenaf and Other Cellulosic Fibers

Abstract: Currently, there is a major upsurge in research on the use of recyclable and biodegrad able materials in manufactured products. This has triggered a need for biodegradable nonwovens for nearly forty automotive interior components, which currently contain traditional materials such as glass and other manufactured fibers and foams that are difficult to recycle. By incorporating agricultural lignocellulosic (bast) fibers such as kenaf, jute, hemp, and flax in the manufacture of automotive nonwovens, their biode g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Since it was experimentally observed that the rare earth luminescence efficiency at room temperature increases with the band gap of the semiconductor [2], wide band gap materials such as GaN are especially promising for possible applications. Rare earth luminescence from Nd, Sm, Eu, Tb, Dy, Ho, Er and Tm has also been reported in the hexagonal II-VI semiconductor ZnO [3][4][5][6][7][8][9][10][11][12]. Interest in zinc oxide has recently increased due to the fact that its structural and semiconducting properties are similar to hexagonal GaN, but that, in comparison to GaN, highquality single crystals of ZnO are easier to grow [13].…”
Section: Cern-ep Ch-1211 Geneva 23 Switzerlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was experimentally observed that the rare earth luminescence efficiency at room temperature increases with the band gap of the semiconductor [2], wide band gap materials such as GaN are especially promising for possible applications. Rare earth luminescence from Nd, Sm, Eu, Tb, Dy, Ho, Er and Tm has also been reported in the hexagonal II-VI semiconductor ZnO [3][4][5][6][7][8][9][10][11][12]. Interest in zinc oxide has recently increased due to the fact that its structural and semiconducting properties are similar to hexagonal GaN, but that, in comparison to GaN, highquality single crystals of ZnO are easier to grow [13].…”
Section: Cern-ep Ch-1211 Geneva 23 Switzerlandmentioning
confidence: 99%
“…Several methods for producing RE-doped ZnO have been described in the literature, including sintering [3][4][5], wet-chemical synthesis [6,11], laser ablation [7-10] and co-deposition following evaporation [12]. However, all these methods result in polycrystalline samples, and there exists evidence that the rare earths accumulate at the grain boundaries of polycrystalline ZnO [4].…”
mentioning
confidence: 99%
“…[26][27][28][29] Incorporating kenaf in the manufacture of automotives not only increased their biodegradability but also reduced their weight and enhanced their noise absorbent ability. Parikh et al 30 found that nonwovens made of retted kenaf blended with cotton fibers, recycled polyester, and off-quality polypropylene could meet industry specifications of flammability, odor, mildew, and strength. Mueller and Krobjilowski 31 have studied the formation of composites by using flax fibers and biodegradable melt-blown polymeric materials as the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds with MCS calculations. In all cases, no emission related to Eu 3+ was observed, because the excitation wavelength is lower than 385 nm [23] and the 4.7 eV (260 nm) photons are not in resonance with any transitions of Eu 3+ ions. It is also worth noting that the intensity ratio of I NBE to I DLE is increasing with the synthesis pressure, as seen in Fig.…”
Section: Spectroscopic Propertiesmentioning
confidence: 93%